Cerminan Etika Profetik dalam Novel Di Kaki Bukit Cibalak Karya Ahmad Tohari Sebagai Media Pendidikan Karakter Peduli Sosial Pascapandemi - Fanie Yuniar Krismonita (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2021)
This study aims to describe prophetic ethics in the novel Di Kaki Bukit Cibalak by Ahmad Tohari as a source of character education. This study uses a qualitative approach. From the results of the study, it was found that the ethics of humanization in the novel Di Kaki Bukit Cibalak covers the personality aspect in the form of not distinguishing between humans. The liberation ethics of the novel Di Kaki Bukit Cibalak found include forms of activity that free oneself and others from political oppression and economic injustice. The transcendence ethic was found to include a sense of surrender to God in any situation, namely qanaah and tawakkal. In post-pandemic situations that still use distance learning, literary works can be an alternative as a medium for planting character education. The three aspects contained in the novel Di Kaki Bukit Cibalak can be used as learning media in instilling the components of social care education.